Intermediate Windows presentation foundation : mastering core concepts of WPF and XAML to move your apps from basic to pro - Long, Mark (O'Reilly, 2016)
"Novice developers working with WPF/XAML understand the basics of how to use layout panels and controls to make user interfaces for apps that often look, feel, and function basic. Wouldn't it be great if those same interfaces could be made more polished, more scalable, more functional, and easier to use? WPF wizard Mark Long shows you how in this entertaining and engaging course covering five key functionalities of WPF: Dependency properties, data binding, templates, triggers and dialogs. Master your understanding of these core concepts says Long and your Windows apps will become masterful too."--Resource description page.